Evaluation of biosynthesis parameters, stability and biological activities of silver nanoparticles synthesized by Cornus Officinalis extract under 365 nm UV radiation. Issue 45 (21st July 2020) - Wang, Yinghui; Wei, Simin; Wang, Kang; Wang, Zhe; Duan, Jinwei; Cui, Lin; Zheng, Huayu; Wang, Ying; Wang, Shanshan
Abstract : We present herein a systematically evaluation of the biosynthesis parameters on the green synthesis of AgNPs by utilizing Cornus officinalis extract under 365 nm UV radiation. Abstract : Since silver nanoparticles (AgNPs) synthesized by using plant extracts revealed varied biological activities, the green synthesis of AgNPs has attracted considerable attention. Although the green synthesis of AgNPs have been accomplished by using the extracts of Cornus Officinalis, which is a traditional Chinese medicine and exhibits a wide spectrum of phytochemicals. The effects of biosynthesis parameters on reducing reaction, stability and more broad biological activities of so-prepared AgNPs did not been evaluated. In this paper, we firstly assessed the effects of UV radiation, pH, material proportion and radiation times on the green synthesis of AgNPs under 365 nm UV radiation by UV-visible spectrum and dynamic light scattering (DLS) analysis. The results showed that UV radiation could accelerate the formation of AgNPs and influence the average size below pH 7.0, and the size of so-prepared AgNPs were sensitive to the pH and material proportion, but no obvious changes to UV radiation times, offering a size-controlled synthetic method for AgNPs. The further X-ray diffraction (XRD), transmission electron microscopy (TEM) and DLS studies showed AgNPs synthesized at pH 7.0, extract: AgNO3 = 1 : 1 and after 4 h UV radiation were a face-centered cubic (fcc) structure and both spherical and polygonal in shape with average particle size of 64.5 ± 0.3 nm existed in a monodispersed form. Subsquently, the stability of AgNPs was analyzed by zeta potential (−24.8 mV) and the average size measurement after 30 days storage (63.3 ± 0.4 nm), revealing a high degree of stability. Lastly, the investigation of biological activities showed that the biosynthesized AgNPs had potent antioxidant activity, antimicrobial activity against both S. aureus and E. coli as well as anticancer activity against HCT116 and HepG2 cell lines but negligible cytotoxicity against SW620. And the internalization of biosynthesized AgNPs inside the bacterial cell was evaluated by flow cytometric analysis, where the SSC values have significant increase after treating with nanoparticles. These results confirmed that the biosynthesis parameters on the green synthesis of AgNPs by using Cornus Officinalis extract also played pivotal roles and so-prepared AgNPs would be useful for the development of new alternative antioxidant, antimicrobial and anticancer agents in biomedicine.